Uncover the roots of challenging behavior create responsive environments where young children thrive - Salcedo, Michelle 1966- (Free Spirit Publishing Inc., 2018)
"Book for educators on how to reduce behavior problems and nurture the growth of all learners in early childhood classrooms. This book guides early childhood teachers to analyze their classroom elements, routines, and responses to children in order to address problem behaviors. Digital content included" --Provided by publisher.